1981
DOI: 10.1099/0022-1317-52-1-183
|View full text |Cite
|
Sign up to set email alerts
|

A Glycoprotein Specified by Spleen Focus-forming Virus in Three Cell Lines Varies in Molecular Size and Peptide Composition, but Retains both Xenotropic and Ecotropic MuLV Antigenicity

Abstract: SUMMARYA glycoprotein with an approx, mol. wt. of 55000, encoded by spleen focus-forming virus (SFFV), was detected with an antiserum against xenotropic murine leukaemia virus (MuLV) in various cell lines infected with the Friend strain of SFFV, suggesting that the SFFV-specific RNA coding for gp55 is related to the xenotropic virus. The proteins from three cell lines differed from each other in molecular size and gave different peptide maps. The differences in the gp55 molecules were shown to depend on differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1983
1983
1984
1984

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In contrast, gp55 is observed in the cells infected with any SFFV strain and has been relatively well characterized in the examination of its role in leukemogenesis (3,9). Although the molecular size and details of the peptide map of gp55 are somewhat variable depending on the SFFV strain (10), the gp55s coded for by different SFFV strains have a common structural property: they are immunologically crossreactive with gp7O, the major viral envelope glycoprotein, of the ecotropic murine leukemia virus (MuLV) (4)(5)(6). Analysis of the SFFV genome 32S RNA by molecular hybridization (11), oligonucleotide fingerprinting (12,13), or heteroduplex formation (14) has indicated that the defective env gene region of SFFV coding for gp55 is composed of the sequence homologous to the env gene sequence of the ecotropic Friend MuLV (F-MuLV) and also of the specific sequence partially homologous to the env gene sequences of the xenotropic MuLVs.…”
mentioning
confidence: 99%
“…In contrast, gp55 is observed in the cells infected with any SFFV strain and has been relatively well characterized in the examination of its role in leukemogenesis (3,9). Although the molecular size and details of the peptide map of gp55 are somewhat variable depending on the SFFV strain (10), the gp55s coded for by different SFFV strains have a common structural property: they are immunologically crossreactive with gp7O, the major viral envelope glycoprotein, of the ecotropic murine leukemia virus (MuLV) (4)(5)(6). Analysis of the SFFV genome 32S RNA by molecular hybridization (11), oligonucleotide fingerprinting (12,13), or heteroduplex formation (14) has indicated that the defective env gene region of SFFV coding for gp55 is composed of the sequence homologous to the env gene sequence of the ecotropic Friend MuLV (F-MuLV) and also of the specific sequence partially homologous to the env gene sequences of the xenotropic MuLVs.…”
mentioning
confidence: 99%